Renal failure and its treatment. Issue 7 (July 2021) - Mishra, Monalisa; Ng, Sarah; Hanison, James
Abstract: Acute kidney injury (AKI) is a common complication of acute illness. It is associated with signicant morbidity and mortality as well as a high cost to healthcare systems. There are a broad range of causes of AKI which should be considered in a systematic fashion to avoid missing multiple potential causative factors. These include pre-renal causes from hypovolaemia, intrinsic renal causes such as glomerular diseases and post-renal obstructive causes. In the intensive care unit, two-thirds of AKI cases result from renal hypoperfusion, sepsis, contrast and nephrotoxic agents; up to 5% will require renal replacement therapy. Modalities of renal replacement therapy include intermittent haemodialysis, peritoneal dialysis and continuous haemoltration. Continuous haemoltration is usually favoured in the intensive care setting as it has greater haemodynamic stability and greater capacity to extract uid from patients with fluid overload. Anticoagulation options can be achieved with systemic anticoagulation such as heparin or regional anticoagulation with citrate.